2022
DOI: 10.1021/acs.orglett.2c01739
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regioselective [5 + 1] Annulation of Vinyl Aziridines/Epoxides with ClCF2COONa

Abstract: Scheme 1. [Pd II ]CF 2 -Involved Transfer Reactions Letter pubs.acs.org/OrgLett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…66 Scheme 27 Synthesis of α,β-unsaturated-δ-lactams and lactones by Li's approach. 65 [3 + 3] cycloaddition reaction to accomplish an array of bi-and tri-heterocyclic scaffolds 83, 84-86 in a moderate yield (up to 73%). In this strategy, not all the aldehydes were successful in the cycloannulation reaction.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Scheme 27 Synthesis of α,β-unsaturated-δ-lactams and lactones by Li's approach. 65 [3 + 3] cycloaddition reaction to accomplish an array of bi-and tri-heterocyclic scaffolds 83, 84-86 in a moderate yield (up to 73%). In this strategy, not all the aldehydes were successful in the cycloannulation reaction.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Zhang's group 63 and Song's group 64 utilized difluorocarbene reagents for fluoroalkylations via a Pd( ii )–CF 2 H intermediate and fluorination via Pd( ii )CF 2 in the presence of H 2 O to release a CO source for a [4 + 1] annulation reaction. In addition to reports in the literature, Li and co-workers 65 recently reported the Pd-catalyzed synthesis of δ-lactams by utilizing vinyl aziridines 56 with ClCF 3 CO 2 Na 76 as a carbonyl source in a [5 + 1] cycloaddition reaction (Scheme 27). The initial study showed that the success of [5 + 1] cycloaddition relies on the presence of Pd(OAc) 2 , PCy 3 , and K 2 CO 3 in dry DMF.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a difluorocarbene-involved (161) reaction of π-allyl Pd(II) complexes (Scheme 30path a). 54 In 2023, Song et al synthesized chiral γ-lactams (167) through an isothiourea (166, ITU)/iridium (164) co-catalyzed reaction of vinyl aziridines (163) with pentafluorophenyl esters (162). This methodology allowed the achievement of several optically active compounds in good yields and with high asymmetric induction (up to 98% ee) (Scheme 30path b).…”
Section: Ring Enlargementsmentioning
confidence: 99%
“…The authors reported a difluorocarbene-involved ( 161 ) reaction of π-allyl Pd( ii ) complexes (Scheme 30 – path a). 54…”
Section: Reactions Of Aziridinesmentioning
confidence: 99%
“…8 Song's group developed an elegant Pd-catalyzed [4 + 1] annulation of 2-iodobiphenyls with ClCF 2 CO 2 Na. 9 Additionally, we disclosed a Pd-catalyzed regioselective [5 + 1] annulation of vinyl aziridines/epoxides with ClCF 2 COONa. 10 Inspired by employing difluorocarbene as carbonyl source 8−10 and the preiodination strategy of indoles, 5b we herein developed a practical and efficient Pd-catalyzed, iodine-assisted carbonylation of indoles using ClCF 2 CO 2 Na and alcohols.…”
mentioning
confidence: 99%